From Hybrid Spaces to In‐between Spaces: A Journey with Contemporary Art and Situated Knowledge. - Jové, Glòria; Gutiérrez‐Ujaque, Daniel; Bonastra, Quim; Simón‐Martín, Meritxell (International Journal of Art & Design Education, 2022)
Theoretical knowledge taught in the classroom forms the bulk of lectures in Initial Teacher Training today. Persuaded that knowledge constructed in the community ought to permeate Teacher Training, Zeichner has developed the notion of Hybrid Space – a space for reflection, training and educational improvement where the background of academic/professional knowledge merges to create new learning opportunities, and where the voices of all participants emerge inclusively. Drawing on but also nuancing Zeichner's Hybrid Space, this paper examines how (1) incorporating working with (in, about, through) contemporary art into our teaching, and (2) putting this pedagogical approach into play by means of situated learning contexts that work with and in the community offers the opportunity to create an innovative teaching approach. This innovation takes the form of transdisciplinary and nomadic learning inputs that operate within an in‐between space and result in unique and unrepeatable learning experiences for all the participants involved.